International Cooperation Between Indonesia and Russia in The Eradication of Corruption (Transnational Crime) (Universitas Negeri Semarang, 2022)
Since the start of the era of globalization, many countries have opened their borders in order to facilitate the exchange of information and the movement of people and goods, creating a borderless situation. The ease of interaction and activities on the one hand has a positive impact including creating a conducive economic situation, but at the same time on the other hand it also brings the threat of increasing crimes that are transnational in nature. The perpetrators of these crimes take advantage of differences in the structure and interpretation of law between countries and state sovereignty to avoid being chased by law enforcement officials. For Indonesia, participation in an MLA collaboration is a manifestation of Indonesia's role in international relations to overcome international problems that can threaten economic, political and legal stability. So far, Indonesia has been active in initiating MLA agreements with other countries to assist domestic law enforcement. As of August 2020, Indonesia has ratified ten MLA agreements with law. In addition to the agreement, Indonesia is also currently completing the process for the ratification of one other agreement, namely with Russia. Using a normative juridical method through a literature study that examines primary and secondary legal materials, this paper will discuss the implementation of Treaty between the Republic of Indonesia and the Russian Federation on Mutual Legal Assistance in Criminal Matters, especially in the crime of corruption.